IMPLEMENTASI GREEN GOVERNANCE DALAM PENGEMBANGAN DESA WISATA ADAT OSING KEMIREN - Siti Mudhawamah (Halu Oleo University, 2025)
Implementation of Green Governance in the Development of the Osing Kemiren Traditional Tourism Village. This study aims to explain the implementation of Green Governance policies in the development of the Osing Kemiren Traditional Tourism Village, analysed using George Edward III's policy implementation theory. This study employed descriptive qualitative methods, and data collection techniques included interviews and documentation. The results indicate that the implementation of green governance in the Kemiren tourism village has been running well, as evidenced by the fulfilment of several indicators, namely communication, resources, and bureaucratic structure. However, problems remain in the disposition indicator, namely, the attitude and commitment of the Kemiren tourism village managers to managing the tourism village. This should be supported by intersectoral collaboration, including the involvement of the private sector. However, in practice, the local government has not yet implemented this intersectoral collaboration, including in waste management in the tourism village.